Women and IPM: Crop Protection Practices and Strategies - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
E van der Fliert and J Proost. Royal Tropical Institute Intermediate Technology Publications, co-publication, 1999. 105 pp.ISBN 90 6832 710 0.H l29.00 Euro 13.15Royal Tropical Institute, KIT Press,PO Box 95001, 1090 HA Amsterdam, The...